In vitro and in vivo Study of Antifungal Effect of Pyrvinium Pamoate Alone and in Combination With Azoles Against Exophiala dermatitidis - Sun, Yi; Gao, Lujuan; Yuan, Mingzhu; Yuan, Lu; Yang, Ji; Zeng, Tongxiang (Frontiers in Cellular and Infection Microbiology, 2020)
Infections of Exophiala dermatitidis are often chronic and recalcitrant. Combination therapies with novel compounds and azoles could be an effective solution. Previously, we have demonstrated that pyrvinium pamoate exerted antifungal activity alone and favorable synergy with azoles against planktonic E. dermatitidis. Herein, the underlying antifungal mode of action were investigated. Pyrvinium alone showed sessile MIC50 (SMIC50) of 8->16 μg/ml against E. dermatitidis biofilms. However, synergism of PP with itraconazole, voriconazole, and posaconazole were observed against 16 (88.9%), 9 (50%), and 13 (72.2%) strains of E. dermatitidis biofilms. In accordance with in vitro susceptibilities, pyrvinium alone at concentration of 2 μg/ml resulted in significant growth restriction of planktonic E. dermatitidis. Pyrvinium alone resulted in reduction of biofilm formation. Higher concentration of pyrvinium was associate with more progressive reduction of biofilm mass. The in vivo activity of pyrvinium alone and combined with azoles was evaluated using Galleria mellonella model. Pyrvinium alone significantly improved the survival rate of larvae (P < 0.0001). The combination of pyrvinium and voriconazole or posaconazole acted synergistically in vivo (P < 0.05). Fungal burden determination revealed significant reduction of numbers of colony forming unit (CFU) in larvae treated with pyrvinium-itraconazole and pyrvinium-posaconazole compared to itraconazole or posaconazole alone group, respectively. The effect of pyrvinium on apoptosis, expression of TOR and HSP90, and drug efflux reversal were evaluated by PI/Annexin V staining, Real-Time Quantitative PCR and Rhodamine 6G assay, respectively. Pyrvinium alone or combined with azoles significantly (P < 0.05) increased late apoptosis or necrosis of E. dermatitidis cells. Pyrvinium combined with posaconazole significantly decreased the expression of TOR and Hsp90 compared to posaconazole alone group (P < 0.05). Pyrvinium resulted in significant (P < 0.05) decrease of the efflux of Rhodamine 6G. These findings suggested pyrvinium could be a promising synergist with azoles. The underlying mechanisms could be explained by inducing apoptosis/necrosis, inhibition of drug efflux pumps, and signaling pathways related with stress response and growth control.